An Analysis of Anti-Spoof Mechanisms in Face Liveness Detection - Singh, Samarth; Pandey, Prajjwal; S, Thenmalar (International Journal of Psychosocial Rehabilitation, 2020)
One of the most generally used framework to recognize the authorized person based on behavioral or physical characteristics is the Biometric system. One of the present issues with this system is that it can be easily spoofed. A spoofing attack is nothing but a situation in which a person or a program successfully identifies themselves as another person in order to use the system without the permission of authorized user thus harming or attacking the biometric recognition system. The biometric system can be easily spoofed by methods such as using face images of the authorized person, masks or videos which are easily available on social media these days. In this analysis, categorization of face liveness detection is done based on different techniques used for detecting spoofing attacks. This helps in inferring various developed solutions and spoofing attacks associated with them. An investigation of late examinations in the field of face liveness discovery has been laided to provide a simple and clear path for future improvement in the field of face liveness detection.